Australian and New Zealand women teachers in the First World War. Issue 1 (3rd June 2019) - Morris Matthews, Kay; Whitehead, Kay
Abstract : Purpose: The purpose of this paper is to highlight the contributions of women teachers to the war effort at home in Australia and New Zealand and in Egypt and Europe between 1914 and 1918. Design/methodology/approach: Framed as a feminist transnational history, this research paper drew upon extensive primary and secondary source material in order to identify the women teachers. It provides comparative analyses using a thematic approach providing examples of women teachers war work at home and abroad. Findings: Insights are offered into the opportunities provided by the First World War for channelling the abilities and leadership skills of women teachers at home and abroad. Canvassed also are the tensions for German heritage teachers; ideological differences concerning patriotism and pacifism and issues arising from government attitudes on both sides of the Tasman towards women's war service. Originality/value: This is likely the only research offering combined Australian–New Zealand analyses of women teacher's war service, either in support at home in Australia and New Zealand or working as volunteers abroad. To date, the efforts of Australian and New Zealand women teachers have largely gone unrecognised.